2012
DOI: 10.5657/fas.2012.0091
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Nonylphenol-degrading Bacteria

Abstract: To isolate a nonylphenol (NP)-degrading bacterium, we isolated a single colony from the NP-degrading microbial consortium SW-3, which was previously isolated from an aqueous environment. Ten colonies that exhibited different cell morphologies were isolated and the strains were named SW- 3-A, -B, -C, -D, -E, -F1, -F2, -G, -H, and -I. The ability of isolates to degrade NP was evaluated by kinetic analysis by the constant of NP degradation rate (k 1 ) and the half-life time of NP degradation (t 1/2 ). SW-3-F1, -F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…NPEO x and its derivative degrading bacterial strains have been isolated from several natural environments and wastewater treatment plants [1, 5, 21, 30, 5759]. In this paper the reported data indicated that indigenous bacterial strains, isolated from soil, are able to use NPEO 15 as the sole carbon source.…”
Section: Resultsmentioning
confidence: 91%
“…NPEO x and its derivative degrading bacterial strains have been isolated from several natural environments and wastewater treatment plants [1, 5, 21, 30, 5759]. In this paper the reported data indicated that indigenous bacterial strains, isolated from soil, are able to use NPEO 15 as the sole carbon source.…”
Section: Resultsmentioning
confidence: 91%
“…The same steps were followed in the effect of temperature, but the temperature was fixed at 37 ° C, with different concentrations (0.5, 1, 1.5, 2 & 3%) of crude oil incubated at 37 °C in a shaker incubator of 150 rpm for 12 days. After the incubation period, the biodegradation of the crude oil for both control and bacterial isolates was determined by spectrophotometry at 600 nm wavelength (Gupta, 2012).…”
Section: The Effect Of Crude Oil Concentrationmentioning
confidence: 99%
“…Bacterial species and genera that have been reported to degrade NP and NPEs include Ochrobactrum sp., Staphylococcus sp., Achromobacter sp., Alcaligenes sp. (Yu et al, 2012), Sphingomonas cloacae (Pluemsab et al, 2007), the genera Pseudomonas, Sphingomonas, Sphingobium, Cupriavidus, Ralstonia, Achromobacter, Staphylococcus (Gu et al, 2010), and Pseudomonas spp. (Yuan et al, 2004;Chakraborty and Dutta, 2006;Liu et al, 2006;Watanabe et al, 2012).…”
Section: Phenolics As Electron-donor Sources For Molybdenum Reductionmentioning
confidence: 99%